KARAKTERISTIK MANIFESTASI NEUROLOGIS PADA PASIEN HIV/AIDS DI RUMAH SAKIT PUSAT ANGKATAN DARAT GATOT SOEBROTO TAHUN 2020 - 2021 - Salsabila Syahira, (2022)
Acquired Immunodeficiency Syndrome (AIDS) is a collection of symptoms due to the weakness of the immune system caused by the Human Immunodeficiency Virus (HIV). The purpose of this study was to determine the characteristics of neurological manifestations in HIV/AIDS patients at the Rumah Sakit Pusat Angkatan Darat Gatot Soebroto (RSPAD) between January 2020 and June 2021. This study is a retrospective descriptive study. The sample of this study were HIV/AIDS patients with neurological manifestations at the Rumah Sakit Pusat Angkatan Darat Gatot Soebroto who met the inclusion criteria. The technique used in this study is a non-probability sampling technique, namely a saturated sample (total sampling). Based on data collection, there were 42 HIV/AIDS patients with neurological manifestations from 104 HIV/AIDS patients. The prevalence rate in this study was 40%, namely 42 patients with neurological manifestations from 104 HIV/AIDS patients. The distribution of the major complaint with the highest proportion was headache in 17 (40%) patients and the distribution of diagnosis with the highest proportion was brain toxoplasmosis in 30 (71%) patients. Based on the results of this study, 35 patients (85 percent) were between the ages of 25 and 49, 35 patients (83 percent) were male, and assessment of CD4 levels <200 l was undertaken on 32 patients (76.2%).